The Persistence of Slowed Time Experience During the COVID-19 Pandemic: Two Longitudinal Studies in France - Droit-Volet, Sylvie; Martinelli, Natalia; Chevalère, Johann; Belletier, Clément; Dezecache, Guillaume; Gil, Sandrine; Huguet, Pascal (Frontiers in Psychology, 2021)
The home confinement imposed on people to fight the COVID-19 pandemic interrupted the flow of time by disrupting daily life, making them feel that time was passing slowly. The aim of this longitudinal study was to evaluate the evolution over time of this subjective experience of time and its significant predictors (boredom, decreased happiness, life rhythm, sleep quality). Two samples of French participants were followed up: the first for several weeks during the first lockdown (April 2020) and then one year later (April 2021) (Study 1), and the second during the first lockdown (April 2020) and then 6 months (November 2020) and 1 year (April 2021) later (Study 2). Our study shows that the French have the feeling that time has passed slowly since the beginning of the first lockdown and that it has not resumed its normal course. This is explained by a persistent feeling of boredom characteristic of a depressive state that has taken hold in the population. The findings therefore suggest that the repeated contexts of confinement did not contribute to re-establishing a normal perception of time, to which a subjective acceleration of time would have testified.